Vitamin D status and tic disorder: a systematic review and meta-analysis of observational studies - Xiaoxia, Lin; Jilong, Jiang; Xianrui, Chen; Yanhui, Chen (Frontiers in Pediatrics, 2023)
Objective: To evaluate the clinical relationship between tic disorders and vitamin D level in children. Methods: Online databases, including CNKI, Wanfang, VIP, Cochrane Library, PubMed and Embase digital knowledge service platform, were checked up to June 2022 for relevant observational studies published in Chinese and English. A random-effects model was incorporated to summarize the study results. The RevMan5.3 software was used for meta-analysis. Results: Out of 132 retrieved articles, 13 observational studies were eligible for inclusion in the systematic review and meta-analysis. The serum vitamin D level in the TD group was lower than that in the HC group (MD = -6.64，95%CI：-9.36 to -3.93，P < 0.001, Heterogeneity test: P < 0.001, I2 = 94%). Subgroup analysis showed no statistically significant differences in serum vitamin D levels between the TTD group and the CTD group (MD = 3.84, 95%CI：-0.59 to 8.26, P = 0.09, Heterogeneity test: P < 0.001, I2 = 90%). There was also no difference in serum vitamin D levels between the CTD group and the TS group (MD = 1.06，95%CI：-0.04 to 2.16, P = 0.0, Heterogeneity test: P = 0.54, I2 = 0%). However, five literatures showed that there was a statistical difference in serum vitamin D level between the TTD group and the TS group（MD = 5.24, 95%CI：0.68～9.80, P = 0.02, Heterogeneity test: P < 0.001, I2 = 92%). Ten literatures showed that there was also a statistically significant difference in the ratio of male children between the TD group and the HC group (OR = 1.48,95%CI：1.07–2.03, P = 0.02,Heterogeneity test: P <0.001, I2 = 74%). There was no statistically significant difference in the age of children between the TD group and the HC group (OR = 0.46，95%CI：-0.33 to 1.24，P = 0.25, Heterogeneity test：P < 0.001，I2 = 96%). Conclusions: Our meta-analysis showed that the vitamin D level of children with TD was lower than that of healthy children. However, there was no difference between the subgroup. Due to the limitations of included studies in research design and diagnostic criteria, large samples, multi-center and high-quality studies are still needed for further analysis and confirmation.